Răspuns :
Răspuns:
Explicație pas cu pas:
a)
(a+4) ((a+4)²-4(a+4)+a+6)=
(a+4) (a²+8a+16-4a-16+a+6)=
(a+4)(a²+5a+6)=(a+4)(a²+2a+3a+6)=
(a+4) (a(a+2) +3(a+2))
(a+4) (a=2) (a=3)
(a+2)(a+3) (a+4)
b) Fie a+2=b
atunci
b(b+1) (b+2), produs de 3 nr intregi consecutive, deci div. cu 6
[tex]\it a)\ \ E=(a+4)(a^2+8a+16-4a-16+a+6)=(a+4)(a^2+5+6)=\\ \\ =(a+4)(a+3)(a+2)\\ \\ \\ b)\ \ a\in \mathbb{Z} \Rightarrow (a+4)(a+3)(a+2)\ \vdots\ 6\ (fiind\ produs\ de\ trei\ numere\ \hat\imath ntregi\ consecutive)\ .\\ \\ Deci,\ E(a)\ \vdots\ 6,\ \ \forall a\in\mathbb{Z}[/tex]